Antimicrobial resistance of Helicobacter pylori in Germany, 2015 to 2018. (February 2020) - Bluemel, B.; Goelz, H.; Goldmann, B.; Grüger, J.; Hamel, H.; Loley, K.; Ludolph, T.; Meyer, J.; Miehlke, S.; Mohr, A.; Tüffers, K.; Usadel, H.; et al.
Abstract: Objectives: National and international guidelines recommend empiric first-line treatments of individuals infected with Helicobacter pylori without prior antimicrobial susceptibility testing. For this reason, knowledge of primary resistance to first-line antibiotics such as clarithromycin is essential. We assessed the primary resistance of H. pylori in Germany to key antibiotics by molecular genetic methods and evaluated risk factors for the development of resistance. Methods: Gastric tissue samples of 1851 yet treatment-naïve H. pylori -positive patients were examined with real-time PCR or PCR and Sanger sequencing for mutations conferring resistance to clarithromycin, levofloxacin and tetracycline. Clinical and epidemiological data were documented and univariable and multivariable logistic regression analyses were conducted. Results: Overall primary resistances were 11.3% (210/1851) to clarithromycin, and 13.4% (201/1497) to levofloxacin; resistance to tetracycline (2.5%, 38/1497) was as low as combined resistance to clarithromycin/levofloxacin (2.6%, 39/1497). Female sex and prior antimicrobial therapies owing to unrelated bacterial infections were risk factors for clarithromycin resistance (adjusted OR (aOR) 2.3, 95% CI 1.6–3.4; and 2.6, 95% CI 1.5–4.5, respectively); older age was associated with levofloxacin resistance (aOR for those ≥65 years compared with those 18–35 years: 6.6, 95% CI 3.1–14.2). Conclusions: Clarithromycin might still be recommended in first-line eradication therapies in yet untreated patients, but as nearly every tenth patient may carry clarithromycin-resistant H. pylori it may be advisable to rule out resistance ahead of treatment by carrying out susceptibility testing or prescribing an alternative therapy.